Avaliação de currículo na opinião dos alunos concluintes de um curso de pedagogia - Eleres, Isabelle Leite Mendes (2009)
This work concerns the Pedagogy graduating student opinion on the Curriculum Evaluation, based on students graduating in the year 2007 at a public university in the state of Pará. This initiative provided the students a space for insertion in the evaluation in order to enhance their participation as one of the interlocutors of the University from the following questions: In the opinion of graduates in 2007, what issues do they consider important in evaluating the Course? The problems identified in the external evaluation are ratified? Are they denied? Such questions have arisen since they have completed their training under the direction of an Educational Project of the Course (EPC) with various limitations and weaknesses regarding their curriculum, according to the external commission of evaluators appointed by the State Board of Education of the State of Pará. The research adopted a Qualitative Approach and was developed from the theoretical deepening on the subject, based on theoretical as Sobrinho (2002), Cappelletti (2005), Afonso (2005), among others. The analysis of documents of this course was used, as the Pedagogical Project, in effect from training period of the subjects. In the data collection the instrument used was a structured questionnaire with closed and opened questions, from the research objectives. The high number of students enrolled in the 4th year of the course in 2007, totaling 90 graduating students, triggered this approach. The questionnaire was administered to 49 subjects, and 48 answered it. 24 out of these were selected for analysis. The work is structured in five chapters. The first one refers to the Introduction, the second one to the theoretical framework on the proposed topic, as well as the contextualization of the course in question, the third chapter covers the methodology used at work and the authors that guide this process as Chizzotti (2006), Ludke (1986), the fourth chapter concerns the analysis of the data collected and how we can rethink the structure of the course from these data, focusing on aspects related to curriculum, assessment and training of educators with the contributions of its students; Finally, in the Final Considerations the gains and difficulties in developing the curriculum of the evaluated course were gathered